1992
DOI: 10.1080/10934529209375845
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of rainwater cistern systems: A review

Abstract: Many parts of the world do not have community water systems or have systems so badly in need of maintenance and repair that individually maintained water systems are still considered to be an appropriate and important source of potable water. The collection of rainwater by individuals using a cistern storage 2123

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…A continuation of this study by Pinfold et al (1993) showed how simple measures such as the use of a tap and mosquito netting can significantly improve the quality of the stored water. It is also noticeable the work of Lye (1992Lye ( , 1998 who studied the status of rainwater harvesting systems in the United States, assessing the presence of microbiological pollutant and recommending best practices in order to minimize the health risk associated with the presence of pathogens and thus maximize the quality of the harvested rainwater. Amin et al (2013) after studying the effects of catchment, first-flush and storage conditions concluded that the microbial quality of harvested rainwater can be improved significantly by the adoption of proper design and maintenance guidelines.…”
Section: Quality Threat 2: Lack Of Maintenance Periodic Cleaning Andmentioning
confidence: 98%
“…A continuation of this study by Pinfold et al (1993) showed how simple measures such as the use of a tap and mosquito netting can significantly improve the quality of the stored water. It is also noticeable the work of Lye (1992Lye ( , 1998 who studied the status of rainwater harvesting systems in the United States, assessing the presence of microbiological pollutant and recommending best practices in order to minimize the health risk associated with the presence of pathogens and thus maximize the quality of the harvested rainwater. Amin et al (2013) after studying the effects of catchment, first-flush and storage conditions concluded that the microbial quality of harvested rainwater can be improved significantly by the adoption of proper design and maintenance guidelines.…”
Section: Quality Threat 2: Lack Of Maintenance Periodic Cleaning Andmentioning
confidence: 98%
“…It can be contaminated by atmospheric lead, airborne herbicides/pesticides, or other contaminants from the roof collection/conveyance system, including fecal contamination from wildlife. As with potable water, microbes can grow in onsite rainwater storage tanks and plumbing (see the group of photographs on page 58) (Fujioka, 1993;Krishna, 1993;Thomas & Greene, 1993;Lye, 1992;Waller, 1989;Yaziz et al, 1989;Body, 1986). These tanks are often sized to hold weeks or months of a building's water demand.…”
Section: Rapid Loss Of Disinfectantsmentioning
confidence: 99%
“…Research on RWH in the U.S. has predominantly focused on water quality associated with RWH systems, such as that published by Lye (), Olem and Berthouex (), Lye (, , ), and Mendez et al . ().…”
Section: Introductionmentioning
confidence: 99%
“…Research on RWH in the U.S. has predominantly focused on water quality associated with RWH systems, such as that published by Lye (1987), Olem and Berthouex (1989), Lye (1992Lye ( , 2002Lye ( , 2009, and Mendez et al (2011). Basinger et al (2010), Damodaram et al (2010), and Jones and Hunt (2010) published research on the performance of U.S. RWH systems; however, Jones and Hunt (2010) was the only U.S.-based study that analyzed the performance of field-installed RWH systems as opposed to modeling theoretical systems and scenarios.…”
Section: Introductionmentioning
confidence: 99%